Development of Weebly-Based Digital Learning Media for Vernier Caliper Material for Class XI Automotive Engineering - Kurniawan Fitri Nugraha; Suhendar Suhendar; Moh Fawaid; Khoirul Munir (VANOS Journal of Mechanical Engineering Education, 2026)
This research was conducted because the problems faced by students regarding vernier calipers in schools have become very complex. The minimal use of technology-based learning media, the lack of infrastructure, and the lack of student interest in learning vernier calipers are things that need to be considered. Therefore, teachers must combine digital learning media and relevant materials that can be used for learning development. The purpose of this study was to determine the development process, the level of validity, and the level of practicality of Weebly-based digital learning media with vernier caliper learning materials. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were students of Automotive Engineering 2, SMKN 2 Tangerang and productive teachers of Automotive Engineering. The results obtained from this study fall into the "very valid" category. Linguists gave a score of 43 with a percentage of 86%, material experts gave a score of 47 with a percentage of 94% and media experts gave a score of 46 with a percentage of 92%. Furthermore, the results obtained from the responses of teachers and students fell into the "very practical" category with a percentage of 95% with a score of 285. Thus, it can be concluded that the learning media developed is valid and practical for use in the learning process.